Indoor Pool Game and Substance Abuse as Trajectories to Students’ Academic Procrastination: The Mediation Role of Self-Regulation - Gita, Dinaol Urgessa; Koya, Amanuel Tadesse; Worku, Berhanu Nigussie (Frontiers in Psychology, 2022)
Background Over the last decade, indoor pool games (IPGs) and substance abuse (SA) became a remarkable emerging addictive behavior among adolescent university students. With the failure of educational quality and retention of learners, boomerangs around the university local environment in line with the students’ learning culture were not considered in many countries including Ethiopia. Thus, this study aimed to examine the trajectory and contribution of an IPG and SA to students’ academic procrastination (AP) as determinants of quality education. Methods A sequential explanatory mixed-methods design was employed. Self-reporting questionnaires, interview guides, and an observation checklist were used to collect data. All self-reporting items were adapted from previous scales. By using simple random sampling techniques, 237 undergraduate university students were selected for obtaining the quantitative data, and using purposive sampling, 12 interviewees were selected to collect the qualitative data. The SPSS AMOS version 25 was used to compute the multiple mediation path analysis. The Hayes PROCESS macro model was used. Furthermore, the thematic content analysis method was employed for the qualitative data. Results A direct path analysis was established between IPG, SA, and AP. The path analysis model indicated that IPG did not significantly predict AP. Moreover, SA significantly predicted AP. In addition, SR had a partial mediating effect on the relationship between IPG, SA, and AP. Conclusion The study concluded that IPG and substances available around the university local environment found trajectories to students’ AP, which in turn affects the quality of education.